STRATEGI KOMUNIKASI PARIWISATA PEMERINTAH KABUPATEN TOBA DALAM MENYUKSESKAN EVENT F1H2O - Sihombing, Bantors; Panjaitan, Hadi (Jurnal Ilmiah Akomodasi Agung, 2024)
Tourism development has become a primary focus for many local governments aiming to boost their economies and enhance the popularity of their tourist destinations. The Toba Regency Government is an exemplary entity actively promoting regional tourism. One of their initiatives is organizing the F1H2O speedboat racing event on Lake Toba. In this paper, we analyze the communication strategies employed by the Toba Regency Government in formulating and implementing tourism programs related to the F1H2O event. The research adopts a qualitative descriptive method, involving document analysis and observation of various promotional activities carried out by the local government. The findings reveal several effective communication strategies utilized by the Toba Regency Government, including social media campaigns, collaboration with private entities, and online channel promotions. Consequently, this study provides valuable insights for other local governments seeking to strengthen their tourism sectors through internationally acclaimed events.